2006
DOI: 10.1381/096089206778870157
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy in the High-Risk Patient

Abstract: Although the sleeve gastrectomy does not result in as much weight loss as the duodenal switch or gastric bypass, it can be used as a stand-alone operation or as a bridge to more complex procedures in the high-risk super-obese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(117 citation statements)
references
References 15 publications
5
104
1
7
Order By: Relevance
“…Laparoscopic sleeve gastrectomy is associated with a significant improvement of T2DM and other obesity-associated comorbidities such as hypertension and hyperlipidemia (13,14). Postoperative improvement of diabetes starts even before significant weight loss has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic sleeve gastrectomy is associated with a significant improvement of T2DM and other obesity-associated comorbidities such as hypertension and hyperlipidemia (13,14). Postoperative improvement of diabetes starts even before significant weight loss has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…LSG has demonstrated weight-loss results comparable to LRYGB and LBPD-DS but with a lower morbidity profile, associated with improvement of health status and resolution of co-morbidities such as diabetes, hypertension, OSA and dyslipidemia [16,18,38,41,44,45,47,48]. Silecchia et al [44] showed that in 41 super-obese patients (9 patients with BMI > 60 kg/m ) following LSG, 60% of major comorbidities were resolved and 24% improved, 57.8% of patients were co-morbidity-free and 31.5% had only one major co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Leaks and bleeding represent the most feared complications and the most frequently reported causes of death after LSG. Reported leak rates range from 0.7 to 5.3% [24,41,[44][45][46]50]. Esophageal stenting (endoluminal technique) is an effective and new strategy for treatment of gastric fistula, and may be performed safely in a patient with leak of the staple line following sleeve or re-sleeve gastrectomy (for weight regain) with or without BPD-DS [53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure was previously the first part of a more complex mixed operation called the duodenal switch, 80 and it involves the removal of the greater curvature and gastric fundus and a consequent reduction of ghrelin production. [81][82] Vertical gastrectomy is an emergent restrictive bariatric surgery; 83,84 it causes satiety and can be used as an initial stage in a two-stage operation for high-risk surgical patients, [85][86][87] or as an isolated and final surgery. 88 Vertical gastrectomy alone has demonstrated satisfactory results in weight loss, 89 glycemic control 90 and early satiety, even in long-term assessments.…”
Section: Introductionmentioning
confidence: 99%